Find all School-related info fast with the new School-Specific MBA Forum

 It is currently 04 May 2015, 09:10

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# Functions Question

 Question banks Downloads My Bookmarks Reviews Important topics
Author Message
TAGS:
Senior Manager
Joined: 05 Oct 2008
Posts: 272
Followers: 3

Kudos [?]: 119 [0], given: 22

Functions Question [#permalink]  08 Oct 2008, 10:59
Hi, can someone help with understanding the following question. I am not familiar with functions and the way they work. Also, any advice on where I could get material to understand this topic.

For which of the following functions is f(a+b) = f(a) + f(b) for all the positive numbers a and b?

f(x) = f(x square)
f(x) = x+1
f(x) = root x
f(x) = 2/x
f(x) = -3x
Senior Manager
Joined: 04 Jan 2006
Posts: 280
Followers: 1

Kudos [?]: 20 [2] , given: 0

Re: Functions Question [#permalink]  08 Oct 2008, 11:11
2
KUDOS
study wrote:
Hi, can someone help with understanding the following question. I am not familiar with functions and the way they work. Also, any advice on where I could get material to understand this topic.

For which of the following functions is f(a+b) = f(a) + f(b) for all the positive numbers a and b?

f(x) = f(x square)
f(x) = x+1
f(x) = root x
f(x) = 2/x
f(x) = -3x

A) Since; f(x) = f($$x^2$$)
f(a) = $$a^2$$
f(b) = $$b^2$$
f(a) + f(b) = $$a^2 + b^2$$ ---------- (1)
and
f(a+b) = $$(a+b)^2$$ ---------- (2)

(1) is not equal to (2). A is incorrect.

B) Since; f(x) = x + 1
f(1) = 1 + 1 = 2
f(x) + f(1) = (x+1) + 2 = x + 3 ---------- (1)
and
f(x+1) = [x+1] + 1 = x + 2 ---------- (2)

(1) is not equal to (2). B is incorrect.

... Please check Choice C & D for your homework

E) f(x) = -3x
f(a) = -3a
f(b) = -3b
f(a) + f(b) = -3a - 3b = -3(a+b) ---------- (1)
and
f(a+b) = -3(a+b) ---------- (2)

(1) = (2), Choice E is the correct answer.
Intern
Joined: 12 Sep 2008
Posts: 25
Followers: 0

Kudos [?]: 6 [2] , given: 0

Re: Functions Question [#permalink]  08 Oct 2008, 11:32
2
KUDOS
I will attack this problem by back-solving.

First, let a = 2 and b = 3. this makes a+b = 5. Substitute 5 for x, which is a+b, and substitute 2 for f(a) and 3 for f(b).

Now, go through each answer choices by plugging in these values for a, b, and a+b for each function:

a) 5^2 = 2^2 + 3^3 ? 25 = 4+9 ? Nope
b) 5+1 = (2+1) +(3+1)? 6 = 3+4 ? Nope
c) square root (5) = square root (2) + square root (3)? ~2.24 = ~1.41 + 1.73? Nope
d) 2/5 = 2/2 + 2/3 ? 2/5 = 1+ 2/3? Nope
e)-3(5) = -3(2) + -3(3)? -15 = -6 + -9? Yes

Therefore, the answer is E.
Senior Manager
Joined: 05 Oct 2008
Posts: 272
Followers: 3

Kudos [?]: 119 [0], given: 22

Re: Functions Question [#permalink]  08 Oct 2008, 11:37
Thanks, Devilmirror & Brandonslee for the fantastic explanation...

I have given you both +1
Re: Functions Question   [#permalink] 08 Oct 2008, 11:37
Similar topics Replies Last post
Similar
Topics:
Function question 4 16 Nov 2011, 22:58
2 Functions question 2 16 Oct 2011, 00:26
function question 4 02 Sep 2009, 05:35
Function Question 2 02 Jul 2009, 11:45
Function question 5 03 Dec 2006, 07:21
Display posts from previous: Sort by

# Functions Question

 Question banks Downloads My Bookmarks Reviews Important topics

 Powered by phpBB © phpBB Group and phpBB SEO Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.